Complete Genome Sequence of the Predatory Bacterium Ensifer adhaerens Casida A - Williams, Laura E. (Genome Announc, 2017)
We report here the complete genome sequence of the facultative predatory bacterium Ensifer adhaerens strain Casida A. The genome was assembled into three circular contigs, with a main chromosome as well as two large secondary replicons, that totaled 7,267,502 bp with 6,641 predicted open reading frames.